Business-Oriented Simulation Model for a Virtual Power Plant Balancing Renewable Energy and Profitability - Shimahara, Fuki; Sun, Jing (Archives of Business Research, 2025)
The rapid deployment of renewable energy (RE) has intensified concerns about the variability of solar and wind power and the resulting difficulty of maintaining a reliable and economically viable electricity supply. This study develops a profit-enhancing business model for a Virtual Power Plant (VPP) that aggregates solar PV, wind turbines, and battery storage serving residential customers in the Kanto region of Japan. Building on and extending an existing cost structure for VPPs, we formulate a profit-based evaluation model and conduct an annual, hourly simulation using actual 2022 meteorological and demand data. A baseline analysis shows that aggressively using batteries to raise the RE share to 98% leads to a large operating deficit, highlighting a fundamental economic barrier. To mitigate this trade-off, we introduce two operational rules: a “switching price” that dynamically selects between market procurement and contracted generators, and constraints that activate battery charging/discharging only when it is economically favorable relative to the market price. Numerical experiments demonstrate that the proposed strategy achieves a 72% renewable energy ratio while maintaining positive annual profit, suggesting that appropriately designed control rules can simultaneously support RE expansion and sustainable VPP operation.